2016
DOI: 10.1007/s11041-016-9964-0
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Structure Factor on High-Temperature Ductility of Pipe Steels

Abstract: Effects of various factors such as the grain size, the morphology of nonmetallic inclusions, and joint microalloying with boron and titanium on the high-temperature ductility of pipe steels are studied. Physical modeling of the conditions of cooling of the skin of a continuous-cast preform in the zone of secondary cooling in a Gleeble facility is performed. Technical recommendations are given for raising the hot ductility of steels under industrial conditions. Key words: hot ductility, continuous casting of st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 4 publications
(3 reference statements)
0
3
0
Order By: Relevance
“…Uncontrolled non-metallic inclusions in steel may have detrimental effects on mechanical properties such as strength, toughness, and ductility [1][2][3][4][5][6]. Generally, characteristics of the inclusions are modified and optimized by refining slag, calcium treatment or rare earth treatment in molten steel to minimize their harmfulness and eliminate nozzle clogging during casting [7][8][9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Uncontrolled non-metallic inclusions in steel may have detrimental effects on mechanical properties such as strength, toughness, and ductility [1][2][3][4][5][6]. Generally, characteristics of the inclusions are modified and optimized by refining slag, calcium treatment or rare earth treatment in molten steel to minimize their harmfulness and eliminate nozzle clogging during casting [7][8][9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…The process of bending parts in a die with an elastic element was investigated. Calculation of theoretical and practical angles of the spring-back were made, as well as comparison of them in percent [23][24]. Was identified that the use of an elastic element reduces the angle of the part's spring-back.…”
Section: Discussionmentioning
confidence: 99%
“…Manufacturing a finished flange according to the standard pr EN 1092-1 from a rotary forged billet with incomplete filling of the flange profile along the inner diameter is possible with an increase in the allowance in the lower part of the flange or an additional operation of cold rolling from the flange end, which can, in addition to filling the profile, improve the metal structure of the thick part of the flange [17,18,19,20,21,22].…”
Section: Methods Of Researchmentioning
confidence: 99%